(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To describe the patient experience of gastrointestinal endoscopy at Vinmec Times City International General Hospital in 2025. Subjects and methods: His study employed a descriptive cross-sectional design involving 360 patients indicated for gastrointestinal endoscopy at Vinmec Times City International General Hospital from January to July 2025. We used the Gastrointestinal Endoscopy Satisfaction Questionnaire (GESQ), a 21-item instrument reflecting patients’ perceptions of the endoscopy process. Each item was assessed using a 5-point Likert scale, where higher scores indicate better patient experience. Data were analyzed using SPSS 20.0 to determine percentages, means, medians, and standard deviations. Results: Overall, the study revealed that patients at Vinmec Times City International General Hospital had a largely positive experience with gastrointestinal endoscopy. A high percentage of patients reported a good experience in the post-endoscopy phase (95.3%) and with the information provided before the procedure (95.0%). The skills of the healthcare staff also received high praise, with 90.8% of patients reporting a good experience. However, there were some areas for improvement. Notably, 10.8% of patients had a less than good experience regarding the level of pain or discomfort both during and after the endoscopy. More specifically, 6.9% of patients felt pain after the procedure, 7.5% reported that the communication skills of the endoscopy staff were not good, and 5.3% had concerns about the information provided in the referral and consent forms before the endoscopy. Conclusions: Patients undergoing gastrointestinal endoscopy rated the experience as good at a high level. Some areas that need to be focused on to improve the patient experience are pain and discomfort during and after endoscopy, nursing communication, and the consent form.